RELATIVE EFFECTIVENESS OF BRAINSTORMING AND THINKPAIR-SHARE STRATEGIES ON STUDENTS’ ACADEMIC ACHIEVEMENT AND RETENTION IN BIOLOGY (NAU Journal of Technology and Vocational Education, 2024)
The need for higher success in academic achievement of students in biology has always been theconcern of science teachers, educational assessors and evaluator. It is necessary to experimentmore student-centre methods of teaching. This study, therefore, ascertain the effects ofbrainstorming and think-pair-share teaching strategies when compared with the usualconventional teaching method. Two research questions were answered and two correspondinghypotheses were tested. The quasi-experimental research design was employed. One hundredand thirty-nine senior secondary school students were sampled. The biology achievement test(BAT) with multiple choice questions was used as the instrument for data collection. The BATwas subjected to face and content validity, while Kuder-Richardson method was used for thereliability, which yielded a coefficient of 0.71. data were collected as pre-test, post-test, anddelayed post-test. Mean, standard deviation, and analysis of covariance were used as statistictools. Findings revealed that students showed higher academic achievement scores with thethink-pair-share and brainstorming strategies than the conventional method. Nevertheless, nosignificant difference was found between the students taught biology with brainstorming andthink-pair-share strategies. The implication is that students will report higher academicachievement when student-centre methods are employed in teaching biology in secondaryschool.
Keywords: Academic achievement, biology, brainstorming, retention, secondary school, thinkpair-share.